Music and 25% glucose for preterm babies during the pre-procedure for arterial puncture: facial mimics emphasis - Maria Vera Lúcia Moreira Leitão Cardoso; Gleicia Martins de Melo (Universidade Federal de Goias, 2016)
We aimed to describe and quantify facial mimic movements of preterm babies during music and 25% glucose interventions at the pre-procedure for arterial puncture. A randomized controlled trial involving 48 videos of preterm attended in a public neonatal unit, in Fortaleza - Ceará. We collected data from footage analyses during the pre-procedure. Babies heard a lullaby song for 10 minutes in the experimental group; we administered 25% glucose in the control group at the end of the eighth minute, matching a total of 10 minutes of observation. We assessed the frequency of facial expressions: cry, sneeze, yawn, frown the forehead, focused sight, vague sight, sleeping and head movement. Statistically significant variable for the control group: vague sight (p=0.001) at the two last minutes of observation. We concluded that there was no association between most of facial movements and the studied interventions, except for a vague sight in the control group.